Conservation implications of low contemporary connectivity along the Mid‐Atlantic Ridge in hydrothermal vent gastropods - E. Portanier; A. Tran Lu Y; F. Pradillon; C. Daguin‐Thiébaut; S. Ruault; P. Collins; E. Omnes; S. Fuchs; J. Carlsson; D. Jollivet; M. Matabos (Conservation Biology, 2026)
Polymetallic sulfide deposits produced at hydrothermal vent fields are targets for mining exploitation along the Mid‐Atlantic Ridge, threatening the functioning and resilience of vent ecosystems that provide multiple ecosystem services. Knowledge about connectivity between vents will inform conservation practices. The present‐day genetic structure and demographic history of the two vent‐dwelling gastropod species, Lepetodrilus atlanticus and Peltospira smaragdina , were investigated using more than 15,000 single‐nucleotide polymorphisms and mt Cox1 sequences. Each species comprised three genetic groups. Genetic breaks were stronger for L. atlanticus , separating three distinct operational taxonomic units (5°S, Broken Spur at 29°N, and the Azorean vent fields near 37°N). Peltospira smaragdina was also geographically separated into three groups: Broken Spur, TAG, and Snake Pit (23–29°N); Lucky Strike (37°N); and Moytirra (45°N). A semipermeable zone was detected south of Rainbow (35°N), similar to that of vent mussels in this area, suggesting the presence of a multispecies hybrid zone. Demographic inferences supported secondary contact between most pairs of metapopulations for both species, but the time since contact was insufficient for allele frequencies to rehomogenize. Gene flow between vent fields may be sporadic and rare or restricted by genetic barriers. The fragmentation of species into isolated metapopulations may reduce their resilience to disturbance and create the need for specific conservation measures. Isolated populations (e.g., Moytirra for P. smaragdina , 5°S and Broken Spur for L. atlanticus ), source populations (e.g., Lucky Strike for P. smaragdina ), admixture areas, and sites that may act as stepping stones within a metapopulation must be protected from deep‐sea mining. An average distance of

Evolution of Single-Domain Globins in Hydrothermal Vent Scale-Worms - J. Projecto-Garcia; A.-S. Le Port; T. Govindji; D. Jollivet; S. W. Schaeffer; S. Hourdez (Journal of Molecular Evolution, 2017)

Meso-scale hydrodynamic and reproductive asynchrony affects the source–sink metapopulation structure of the coastal polychaete Pectinaria koreni - M. T. Jolly; E. Thiébaut; P. Guyard; F. Gentil; D. Jollivet (Marine Biology, 2014)

Pre-zygotic factors best explain reproductive isolation between the hybridizing species of brittle-stars Acrocnida brachiata and A. spatulispina (Echinodermata: Ophiuroidea) - D. Muths; D. Davoult; M. T. Jolly; F. Gentil; D. Jollivet (Genetica, 2010)

Population genetics and hydrodynamic modeling of larval dispersal dissociate contemporary patterns of connectivity from historical expansion into European shelf seas in the polychaete Pectinaria koreni - M. T. Jolly; P. Guyard; C. Ellien; F. Gentil; F. Viard; E. Thiébaut; D. Jollivet (Limnology and Oceanography, 2009)
Using Pectinaria koreni as a biological model of larval dispersal, we coupled the analysis of differently evolving genetic markers (mitochondrial cytochrome oxidase I and four microsatellite loci) to hydrodynamic modeling of larval transport in the English Channel. To determine the influence of historical and contemporary processes on the genetic structure of our study populations, genetic relationships between English Channel, Irish Sea, and southern North Sea populations were assessed in relation to the long‐term pattern of marine currents and to postglacial colonization pathways. Although significant, low level of overall nuclear genetic differentiation was best explained by the recent origin of populations within the study area and the retention of ancestral polymorphism. Both genetic data sets suggest that two ancestral gene pools contributed to the origin of our study populations, and secondary contacts occurred in the English Channel and southern North Sea as a result of two migration routes around the British Isles. Although Irish Sea and Belgium populations appeared more recently connected, populations of the eastern English Channel were more isolated. English Channel patterns of connectivity indicated high dispersal and gene flow along the French coast, from Normandy to the southern North Sea. Despite significant genetic differentiation between both coasts, migration model selection favored cross‐channel gene flow and long‐distance migration following the coastlines. Our results highlight the influence of postglacial colonization on genetic patterns in the English Channel, and indicate that contemporary mesoscale connectivity inferred by hydrodynamic modeling cannot, alone, explain the present genetic structure of populations in this area.

Comparative phylogeography among hydrothermal vent species along the East Pacific Rise reveals vicariant processes and population expansion in the South - S. PLOUVIEZ; T. M. SHANK; B. FAURE; C. DAGUIN‐THIEBAUT; F. VIARD; F. H. LALLIER; D. JOLLIVET (Molecular Ecology, 2009)
The use of sequence polymorphism from individual mitochondrial genes to infer past demography has recently proved controversial because of the recurrence of selective sweeps acting over genes and the need for unlinked multilocus data sets. However, comparative analyses using several species for one gene and/or multiple genes for one species can serve as a test for potential selective effects and clarify our understanding of historical demographic effects. This study compares nucleotide polymorphisms in mitochondrial cytochrome oxidase I across seven deep‐sea hydrothermal vent species that live along the volcanically active East Pacific Rise. Approximate Bayesian Computation (ABC) method, developed to trace shared vicariant events across species pairs, indicates the occurrence of two across species divergence times, and suggests that the present geographical patterns of genetic differentiation may be explained by two periods of significant population isolation. The oldest period dates back 11.6 Ma and is associated with the vent limpet Lepetodrilus elevatus , while the most recent period of isolation is 1.3 Ma, which apparently affected all species examined and coincides with a transition zone across the equator. Moreover, significant negative Tajima’s D and star‐like networks were observed for all southern lineages, suggesting that these lineages experienced a concomitant demographic and geographical expansion about 100 000–300 000 generations ago. This expansion may have initiated from a wave of range expansions during the secondary colonization of new sites along the Southern East Pacific Rise (founder effects below the equator) or recurrent bottleneck events because of the increase of eruptive phases associated with the higher spreading rates of the ridge in this region.

Geographic clines and stepping-stone patterns detected along the East Pacific Rise in the vetigastropod Lepetodrilus elevatus reflect species crypticism - M. Matabos; E. Thiébaut; D. Le Guen; F. Sadosky; D. Jollivet; F. Bonhomme (Marine Biology, 2008)

Incomplete cryptic speciation between intertidal and subtidal morphs of Acrocnida brachiata (Echinodermata: Ophiuroidea) in the Northeast Atlantic - D. MUTHS; D. DAVOULT; F. GENTIL; D. JOLLIVET (Molecular Ecology, 2006)
The brittle‐star Acrocnida brachiata (Montagu) lives in sandy‐bottom habitat of both intertidal and subtidal zones along the coasts of the northwestern Europe. An allozyme frequency‐based survey (five enzyme loci) was combined with a mitochondrial (mt) COI haplotype analysis (598‐bp sequences) on 17 populations to trace back past colonization pathways from the actual population structure of the species. Both genetic markers display a sharp genetic break between intertidal (clade I) and subtidal populations (clade S). This break corresponds to an allele frequency inversion at three enzyme loci ( Hk , Pgm and Pgi ) and a deep divergence of about 20% in mtCOI sequences between most of the intertidal populations and other samples. The geographic distribution of clade I seems to be more restricted than clade S as it is absent from the intertidal of the eastern English Channel and North Sea and may be replaced by clade S in south Brittany. Applying previously published rates of mutation, divergence between the two clades is estimated to pre‐date 5 million years ago and may be due to allopatric speciation processes at the Mio–Pliocene transition. The occurrence of putative hybrids in a few localities, however, suggests incomplete cryptic speciation with secondary contact zones. The relative importance of colonization history vs. habitat specialization are discussed in the light of neutral evolution as tested from mtCOI gene sequences. While differential selection seems to have contributed little to the separation of the lineages, it may have played a role in the emergence of adaptive polymorphisms in the hybrid zone. Furthermore, congruent spatial patterns of differentiation were observed in both clades suggesting a recent increase in population size. These findings are in agreement with a recent expansion of the populations during or after the formation of the English Channel, from a southern refuge for the subtidal clade whereas the intertidal clade may have persisted further north. As previously suspected for a species with a very short pelagic larval phase, contemporary gene flow between distant or adjacent populations appears to be extremely reduced or even absent.

Comparative phylogeography of two coastal polychaete tubeworms in the Northeast Atlantic supports shared history and vicariant events - M. T. JOLLY; F. VIARD; F. GENTIL; E. THIÉBAUT; D. JOLLIVET (Molecular Ecology, 2006)
The historic processes which have led to the present‐day patterns of genetic structure in the marine coastal fauna of the Northeast Atlantic are still poorly understood. While tectonic uplifts and changes in sea level may have caused large‐scale vicariance, warmer conditions during glacial maxima may have allowed pockets of diversity to persist to a much wider extent than in the Northwestern Atlantic. The large‐scale geographic distribution of deeply divergent lineages of the coastal polychaete tubeworms Pectinaria koreni (two clades) and Owenia fusiformis (three clades) were compared using a fragment of the mitochondrial cytochrome oxidase I gene (mtCOI). All lineages were present along the biogeographic transition zone on the north coast of Brittany (France) and we found evidence pointing towards congruence in the timing of cladogenic events between Pectinaria sp. ( P. auricoma / P. belgica and P. koreni ) and Owenia sp., suggesting a shared history of vicariant events. More conserved 16SrRNA sequences obtained from four species of Pectinariidae together with mtCOI sequences of P. koreni seem consistent with an initial establishment of pectinariids in the north, and a southward colonization of the Northeast Atlantic. Phylogeographic patterns in O. fusiformis were also consistent with a north/south pattern of lineage splitting and congruent levels of divergence were detected between lineages of both species. We observed signatures of both persistence in small northern glacial refugia, and of northwards range expansion from regions situated closer to the Mediterranean. However, whether the recolonization of the Northeast Atlantic by both species actually reflects separate interglacial periods is unclear with regards to the lack of molecular clock calibration in coastal polychaete species.

Introgression patterns in the mosaic hybrid zone between Mytilus edulis and M. galloprovincialis - N. Bierne; P. Borsa; C. Daguin; D. Jollivet; F. Viard; F. Bonhomme; P. David (Molecular Ecology, 2003)
Hybrid zones are fascinating systems to investigate the structure of genetic barriers. Marine hybrid zones deserve more investigation because of the generally high dispersion potential of planktonic larvae which allows migration on scales unrivalled by terrestrial species. Here we analyse the genetic structure of the mosaic hybrid zone between the marine mussels Mytilus edulis and M. galloprovincialis , using three length‐polymorphic PCR loci as neutral and diagnostic markers on 32 samples along the Atlantic coast of Europe. Instead of a single genetic gradient from M. galloprovincialis on the Iberian Peninsula to M. edulis populations in the North Sea, three successive transitions were observed in France. From South to North, the frequency of alleles typical of M. galloprovincialis first decreases in the southern Bay of Biscay, remains low in Charente, then increases in South Brittany, remains high in most of Brittany, and finally decreases again in South Normandy. The two enclosed patches observed in the midst of the mosaic hybrid zone in Charente and Brittany, although predominantly M. edulis ‐like and M. galloprovincialis ‐like, respectively, are genetically original in two respects. First, considering only the various alleles typical of one species, the patches show differentiated frequencies compared to the reference external populations. Second, each patch is partly introgressed by alleles of the other species. When introgression is taken into account, linkage disequilibria appear close to their maximum possible values, indicating a strong genetic barrier within all transition zones. Some pre‐ or postzygotic isolation mechanisms (habitat specialization, spawning asynchrony, assortative fertilization and hybrid depression) have been documented in previous studies, although their relative importance remains to be evaluated. We also provided evidence for a recent migratory ‘short‐cut’ connecting M. edulis ‐like populations of the Charente patch to an external M. edulis population in Normandy and thought to reflect artificial transfer of spat for aquaculture.